Interhemispheric functional connectivity in anorexia and bulimia nervosa. (21st January 2017) - Canna, Antonietta; Prinster, Anna; Monteleone, Alessio Maria; Cantone, Elena; Monteleone, Palmiero; Volpe, Umberto; Maj, Mario; Di Salle, Francesco; Esposito, Fabrizio
Abstract: The functional interplay between hemispheres is fundamental for behavioral, cognitive, and emotional control. Anorexia nervosa (AN) and bulimia nervosa (BN) have been largely studied with brain magnetic resonance imaging (MRI) in relation to the functional mechanisms of high‐level processing, but not in terms of possible inter‐hemispheric functional connectivity anomalies. Using resting‐state functional MRI (fMRI), voxel‐mirrored homotopic connectivity (VMHC) and regional inter‐hemispheric spectral coherence (IHSC) were studied in 15 AN and 13 BN patients and 16 healthy controls (HC). Using T1‐weighted and diffusion tensor imaging MRI scans, regional VMHC values were correlated with the left‐right asymmetry of corresponding homotopic gray matter volumes and with the white matter callosal fractional anisotropy (FA). Compared to HC, AN patients exhibited reduced VMHC in cerebellum, insula, and precuneus, while BN patients showed reduced VMHC in dorso‐lateral prefrontal and orbito‐frontal cortices. The regional IHSC analysis highlighted that the inter‐hemispheric functional connectivity was higher in the 'Slow‐5' band in all regions except the insula. No group differences in left–right structural asymmetries and in VMHC vs. callosal FA correlations were significant in the comparisons between cohorts. These anomalies, not explained by structural changes, indicate that AN and BN, at least in their acute phase, are associated with a loss of inter‐hemispheric connectivity in regions implicated in self‐referential, cognitive control and reward processing. These findings may thus gather novel functional markers to explore aberrant features of these eating disorders. Abstract : The functional interplay between hemispheres has been investigated in anorexia and bulimia nervosa with inter‐hemispheric functional connectivity measures. Compared to healthy subjects, inter‐hemispheric homotopic connectivity and spectral coherence were reduced in anorexia and bulimia patients in regions implicated in self‐referential, cognitive control and reward processing. Inter‐hemispheric connectivity may gather novel functional markers to explore aberrant features of eating disorders.